THE EFFECT OF AUDIT COMMUNITTE ROLE AND INTERNAL CONTROL EFFECTIVENESS AT ISLAMIC BANK INDONESIA - Rini Rini; Yessi Fitri (Faculty of Economics and Business, 2015)
This research examines the effect of audit committee role and internal auditor role on internal control effectiveness. The data is provided from many Islamic banks in Indonesia that was taken by questionnaire from 72 respondents. Questionnaire is consisted of 27 questions. Research instrument contains 9 questions about audit committee role, 8 questions about internal auditor role, and 10 questions on internal control effectiveness. Data analysis used multiple regressions. The result of this research showed that audit committee role and internal auditor role influenced internal control effectiveness simultaneously. Partially, audit committee not significant, but internal auditor influenced internal control effectiveness.